PRODUKTIVITAS TRAKTOR CATERPILLAR D7G DI SUATU PERUSAHAAN HAK PENGUSAHAAN HUTAN DI JAMBI - Dulsalam Dulsalam; Sukanda Sukanda (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
An investigation on the productivity of D7G Caterpillar tractors was carried out at a forest company in Jambi in 1985. Three tractors were selected randomly to be observed. The productivity of these tractors was collected through work time study. The purpose is to find the productivities of D7G Caterpillar tractors so that this information can be used by forest companies in planning skidding operations. This investigation results reveal that : 1. D7G Caterpillar tractors can be used to skid logs at dryland forests having easy and moderate topographies. At skidding distances ranuine from 75 - 535 m with an average of 324 m these tractors can skid logs having volumes ranging from 5.01 - 16.88 m3/trip with an average of 9.08 m3/trip.2. The average productivities of A, B and C skidding tractors were 59.22, 89.81 and 123.69 m8. hm/hour, respectively.The productivities among tractors were significantly different due to different skidding distances, tractor conditions, driver skills, average stund volume per ha, soil conditions, skidded log volume and topography. The average produc- tivity of the three tractors was 92.09 m3 hm/hour.